Теоретико-методичні засади управління ризиками страхових компаній - Подра, О. П.; Петришин, Н. Я.; Podra, O. P.; Petryshyn, N. Ya. (Видавництво Львівської політехніки, 2020)
Висвітлено основні теоретичні та методичні засади управління ризиками страхових компаній в Україні. Досліджено динаміку та особливості розвитку страхового ринку, визначені основні тенденції. Проаналізовано етапи формування комплексних страхових систем управління ризиками, встановлено, що система управління ризиками страхових організацій передбачає ідентифікацію і специфікацію ризиків, визначення цілей і методів управління ризиками, формування і розвиток операційної системи управління ризиками. Здійснено аналіз інноваційних методів управління ризиками, заснованих на використанні EVA та RAROC показників, а також проведено порівняльний аналіз та визначено переваги та недоліки деяких методів аналізу ризиків страхових компаній.

The theoretical and methodological principles of risk management of insurance companies in Ukraine are investigated in the article. The dynamics and features of the insurance market development are studied, the main tendencies are determined. The main risks that significantly affect the existence and development of insurance companies in recent years are external systemic risks – inflation, currency, credit, to such risks are often are added factors that can be called risks with great complexity. The stages of formation of complex insurance risk management systems are analyzed, it is established that the risk management system of insurance organizations provides identification and specification of risks, definition of goals and methods of risk management, formation and development of operational risk management system. The formation of the operating system of risk identification and differentiation is studied. The analysis of innovative methods of risk management based on the use of EVA and RAROC indicators is carried out, as well as the comparative analysis and advantages and disadvantages of some methods of risk analysis of insurance companies. It is established that there are some measures that usually used to limit financial risk in insurance activity they are: reservation of funds in case of negative changes in insurance activity; restrictions on activities or certain types of operations; hedging of financial risks; diversification of financial risk. Despite the existence of different risk management systems, they do not provide fully effective protection of the insurance companies from various financial threats. The insurance market does not have the necessary risk management standards for insurance companies, as a result we can observe its very slow development. Most insurance companies have developed insurance risk management programs, which describe insurance services, goals and policies of risk management and minimization of insurance risks. Thus, the risk management of the entity should be understood as a system of targeted impact on all types of economic risks, which in general allows avoiding or minimizing the negative consequences of their impact on business activity.
Theoretical and methodological aspects of insurance companies’ risk management
Keywords: ризики; страхування; методи; управління ризиками; страховий ринок; страхові компанії; комплексні страхові програми; risks; insurance; methods; risk management; insurance market; insurance companies; complex insurance programs; 336.7.368